Weighting the Indoor Environmental Quality on Work Performance - Tranggono, Tranggono; Anggoro, Radityo; Mukhtarul Haqi, Muhamad; Pramoedya Nugroho, Aldi (Universitas Ahmad Dahlan, 2025)
Poor indoor environmental conditions are often associated with reduced concentration, lower motivation, and decreased productivity in office settings. Addressing this issue requires a systematic assessment of Indoor Environmental Quality (IEQ) and its contribution to work performance. This study examines the effect of Indoor Environmental Quality (IEQ) on office worker performance, focusing on five components: Indoor Air Quality (IAQ), Thermal Comfort, Lighting Quality, Acoustic Quality, and Occupant Experience. The Best-Worst Method (BWM) was applied to determine the relative importance of these factors through a combination of subjective surveys and objective weighting using linear programming. Results indicate that Occupant Experience, particularly ergonomic improvements such as adjustable furniture and optimized layouts, has the strongest influence on productivity. Thermal Comfort ranks second, followed by Lighting Quality, Acoustic Quality, and IAQ. Sensitivity analysis confirms the robustness and consistency of the findings. This research contributes by offering a systematic weighting of IEQ factors, highlighting the central role of ergonomics in workplace design. The study emphasizes that integrating ergonomic and environmental considerations is essential to improve worker performance. The novelty of this study lies in integrating Occupant Experience into the BWM framework, providing a more comprehensive model of IEQ and offering new insights for designing healthier and more productive office environments.